Implementasi Pengaturan Pendaftaran Tanah dalam Pembatalan Peralihan Hak - Supriyadi, Supriyadi; Ratna Sediati, Diah Sulistyani; Dardiri, Nafis (JURNAL USM LAW REVIEW, 2023)
The purpose of this study is to analyze the implementation of Government Regulation Number 24 of 1997 concerning Land Registration in terms of guaranteeing legal certainty and protection to holders of land rights. This study aims to test the effectiveness of the implementation of Government Regulation Number 24 of 1997, especially the application of Article 32 paragraph (2) in the event of cancellation of the transfer of rights. This type of research is normative juridical with a case approach, descriptive analytical research specifications. The results of the study show that the provisions of Article 32 paragraph (2) of Government Regulation Number 24 of 1997 are not effective enough to provide legal protection for land buyers, because the sale and purchase that occurs later by a court decision of the seller is declared bankrupt. The provisions of Article 32 paragraph (2) of Government Regulation Number 24 of 1997 were not considered by the Panel of Judges examining case Number 3/Pdt.Sus–Other Claims/2018/PN.Smg jo. Number 16/Pdt.Sus–Bankrupt/2017/PN Niaga Smg jo. Number 1/Pdt.Sus–PKPU/2017/PN Smg dated 5 September 2018 jo. Number 2 K/PDT.Sus–Bankrupt/2019 February 21 2019, because in the Paulina action case the Panel of Judges provided legal considerations based on the provisions of Article 41, 42 Law Number 37 of 2004 Concerning Bankruptcy and Suspension of Debt Payment Obligations, sale and purchase object of dispute as referred to the Deed of Sale and Purchase Number 340 of 2017 dated August 16 2017, while the seller was declared bankrupt on December 18 2017, the sale and purchase was carried out only 4 (four) months before the bankruptcy decision was pronounced, then the sale and purchase of Property Rights Certificate Number 4086/ The Salatiga sub-district must be cancelled. Tujuan penelitian ini untuk menganalisis implementasi Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah dalam  kaitan jaminan kepastian hukum dan perlindungan kepada pemegang hak atas tanah. Penelitian ini hendak menguji efektifitas Implementasi Peraturan Pemerintah Nomor 24 Tahun 1997 khususnya penerapan Pasal 32 ayat (2) dalam hal terjadinya pembatalan peralihan hak. Jenis penelitian ini adalah yuridis normatif dengan pendekatan kasus, spesifikasi penelitian deskriptif analitis. Hasil penelitian menunjukkan bahwa ketentuan Pasal 32 ayat (2) Peraturan Pemerintah Nomor 24 Tahun 1997 tidak cukup efektif memberikan perlindungan hukum bagi pembeli tanah, karena jual beli yang terjadi kemudian oleh putusan pengadilan penjual dinyatakan pailit. Ketentuan Pasal 32 ayat (2) Peraturan Pemerintah Nomor 24 Tahun 1997 tidak dipertimbangkan oleh Majelis Hakim Pemeriksan perkara Nomor 3/Pdt.Sus–Gugatan Lain-lain/2018/PN.Smg jo. Nomor 16/Pdt.Sus–Pailit/2017/PN Niaga Smg jo. Nomor 1/Pdt.Sus–PKPU/2017/PN Smg tanggal 5 September 2018 jo. Nomor 2 K/PDT.Sus–Pailit/2019 21 Februari 2019, karena di dalam perkara action paulina Majelis Hakim memberikan pertimbangan hukum dengan berpedoman pada ketentuan Pasal 41, 42 Undang Undang Nomor 37 Tahun 2004 tentang Kepailitan Dan Penundaan Kewajiban Pembayaran Utang, jual beli objek sengketa sebagaimana  Akta Jual Beli Nomor 340 Tahun 2017 tanggal 16 Agustus 2017, sedangkan penjual dinyatakan pailit pada tanggal 18 Desember 2017 maka jual beli tersebut dilakukan hanya 4 (empat) bulan sebelum putusan pailit diucapkan, maka jual beli atas Sertifikat Hak Milik Nomor 4086/Kelurahan Salatiga tersebut harus dibatalkan.